A Framework for Strategic Sustainability in Organization: A Three Pronged Approach - Garza, Fernando (Journal of Comparative International Management, 2013)
Sustainability has become an increasingly important strategic concept for organizations. The idea of sustainability is also starting to become ingrained in various managerial and organizational decisions. Sustainability in an organization is defined by its commitment to economic factors, environmental factors, and factors of social commitment in a firm. A framework is used to develop a strategic or long-term justification for the concept of sustainability. Also, this study attempts to extend the concept of sustainability and decision making to a global business environment. This study proposes a mission-driven management methodological framework that acts as a base for decision-making using the concept of international strategic sustainability. This contribution includes investigating the design and development of strategic sustainability and combining the relationships of organizational decision-making to economic, environmental, and social sustainability outcomes.